OFR-38(1)-74 Survey Of Electromagnetic And Seismic Noise Related To Mine Rescue Communications - Volume I - Emergency And Operational Mine Communications ? Introduction - Robert L. Lagace (The National Institute for Occupational Safety and Health (NIOSH), 1974)
This final report documents the work done by Arthur D. Little, Inc. (ADL) on behalf of the U.S. Bureau of Mines, Pittsburgh Mining and Safety Research Center (PMSRC), on Contract R0122026 (which began in August of 1971). Under this contract ADI provided technical assistance to the Bureau on a task basis on virtually all aspects of the Bureau's programs related to present and planned emergency and operational communications and miner location systems for underground coal mines. The work consisted of independent investigations, analyses, experiments, breadboard and prototype hardware development, workshops and technology transfer seminars on mine communications, and on-going evaluations and guidance related to the Bureau's contracted programs on electromagnetic noise, mine communications systems, and trapped miner location. This final report documents the work in two volumes, Volume I, "Emergency and Operational Mine Communications," and Volume II, "Seismic Detection and Location of Isolated Miners." The Tables of Contents of both Volumes are included in each Volume. Phase I of the contract was devoted to performing an in-depth assessment of electromagnetic noise measurements taken by several contractors and other investigators, and then defining a new noise measurement program and instrumentation system tailored to obtain the necessary but missing noise data. These data are required for use in the design of new emergency and operational communication systems. This work, and the follow-on coordination and guidance activities of ADL on this noise measurement program in subsequent phases of the contract, are treated in Part One of Volume I.